Sensory threads of history: a dive into two historical documentaries - Zhenhai Sun; Muye Ma (Cogent Social Sciences, 2024)
Historical documentaries not only involve narrative indexicality and archives, but also dedicate to cultural landscape, distinctive perspectives and ethical enlightenment. So, does this legacy activate sensory experiences? Will it vary by culture? Based on previous research on multimodal discourse analysis (MDA), we hypothesize that it can evoke sensory memory in people, whose meaning-making may differ among cultures. To test the above hypothesis, we establish two multimodal corpora from historical documentaries Frozen Chosin and The Battle of Chosin depicting the same historical event from different cultural perspectives, using ELAN 6.4 to analyze sensory contours of coldness. The findings reveal that filmmakers actualize frostbite-laden experiences by adopting a structural adversity of iciness, with compositional meaning-making as the top, interactive as the second, while the last two are representational and linguistic. Behind this overall homogeneity, the lethal frostbite during engagement and post-battle are heterogeneously mediated by different ways of contacts, perspectives and salience, in which the Chinese film narrates in a slightly convergent multimodality while the American depicts a divergence-prone pattern. Finally, we justify that MDA can help scholars gain deeper insights into the sensory endeavor made by documentarists.